2008
DOI: 10.1211/jpp.60.9.0009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the β-glucuronidase inhibitor saccharolactone on glucuronidation by human tissue microsomes and recombinant UDP-glucuronosyltransferases

Abstract: Glucuronidation studies using microsomes and recombinant UDP-glucuronosyltransferases (rUGTs) can be complicated by the presence of endogenous β-glucuronidases leading to underestimation of glucuronide formation rates. Saccharolactone is the most frequently used β-glucuronidase inhibitor, although as of yet it is not clear whether this reagent should be routinely added to glucuronidation incubations. Here we determined the effect of saccharolactone on eight different UGT probe activities using pooled human liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 29 publications
(36 reference statements)
6
27
0
Order By: Relevance
“…Nakamura et al (2008) used water as an incubation medium for the inhibition study with SL, whereas we used buffered solution (pH 7.4) throughout the experiments. Because SL is an acidic compound, the pH of the incubation medium may be decreased by the addition of 10 mM SL to water, and this may result in nonspecific inhibition (Oleson and Court, 2008). In accordance with this hypothesis, we found complete inhibition of VPA-G deconjugation activity by 10 mM SL in water and confirmed that the pH of the incubation medium was as low as pH 2 under this condition.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Nakamura et al (2008) used water as an incubation medium for the inhibition study with SL, whereas we used buffered solution (pH 7.4) throughout the experiments. Because SL is an acidic compound, the pH of the incubation medium may be decreased by the addition of 10 mM SL to water, and this may result in nonspecific inhibition (Oleson and Court, 2008). In accordance with this hypothesis, we found complete inhibition of VPA-G deconjugation activity by 10 mM SL in water and confirmed that the pH of the incubation medium was as low as pH 2 under this condition.…”
Section: Discussionsupporting
confidence: 86%
“…After a 15-min preincubation of a reaction mixture (72 l) consisting of 1.6 mg/ml human or rat liver cytosol and inhibitors (50 M MEPM or 2 mM SL in 100 mM potassium phosphate buffer, pH 7.4, at 37°C), enzyme reactions were initiated by adding 8 l of substrates: final 50 M VPA-G, 100 M 4-MUG, or 200 M MFA-G. Concentrations of MEPM and SL were selected to completely inhibit the deconjugation reaction of MEPM (see Results) and ␤-glucuronidase (Oleson and Court, 2008), respectively. After incubation at 37°C in a shaking water bath for 40 min, the reaction was terminated by transferring the 20 l aliquot to another tube containing 70 l of water, 10 l of HClO 4 , and 10 l of hexanoic acid (100 M) (internal standard) and then 10 l of KHCO 3 (2 M) was added for neutralization.…”
Section: Methodsmentioning
confidence: 99%
“…Addition of 1 mM UDPGA, PAPS, AcCoA, and SAM did not significantly enhance the reaction rates of glucuronidation, sulfation, N-acetylation, and catechol methylation, respectively. Similarly, the inclusion of 1 mM D-saccharolactone, an inhibitor of b-glucuronidase (Oleson and Court, 2008), did not affect the glucuronidation rate of 4-methylumbelliferone. Since conjugation with glutathione may also proceed as a nonenzymatic reaction (Satoh, 1995), the assays were not performed in a medium supplemented with glutathione.…”
Section: Resultsmentioning
confidence: 90%
“…In some instances saccharolactone has been shown to preserve the glucuronide (Bauman et al, 2005). However, in other instances, saccharolactone did not increase glucuronide formation rates, and in fact, even lowered the glucuronide formation levels (Kaivosaari et al, 2008;Oleson and Court, 2008;Walsky et al, 2012a). It is the authors' opinion and experience that saccharolactone is not necessary due to its potential detrimental effects; hence, it can be excluded from in vitro incubations.…”
Section: Advances In Reaction Phenotypingmentioning
confidence: 96%